Cardiac remodeling following reperfused acute myocardial infarction is linked to the concomitant evolution of vascular function as assessed by cardiovascular magnetic resonance - Huttin, Olivier (J Cardiovasc Magn Reson, 2017)
BACKGROUND: Left ventricular (LV) remodeling following acute myocardial infarction (MI) is difficult to predict at an individual level although a possible interfering role of vascular function has yet to be considered to date. This study aimed to determine the extent to which this LV remodeling is influenced by the concomitant evolution of vascular function and LV loading conditions, as assessed by phase-contrast Cardiovascular Magnetic Resonance (CMR) of the ascending aorta. METHODS: CMR was performed in 121 patients, 2–4 days after reperfusion of a first ST-segment elevation myocardial infarction and 6 months thereafter. LV remodeling was: (i) assessed by the 6-month increase in end-diastolic volume (EDV) and/or ejection fraction (EF) and (ii) correlated with the indexed aortic stroke volume (mL.m(−2)), determined by a CMR phase-contrast sequence, along with derived functional vascular parameters (total peripheral vascular resistance (TPVR), total arterial compliance index, effective arterial elastance). RESULTS: At 6 months, most patients were under angiotensin enzyme converting inhibitors (86%) and beta-blockers (84%) and, on average, all functional vascular parameters were improved whereas blood pressure levels were not. An increase in EDV only (EDV+/EF-) was documented in 17% of patients at 6 months, in EF only (EDV-/EF+) in 31%, in both EDV and EF (EDV+/EF+) in 12% and neither EDV nor EF (EDV-/EF-) in 40%. The increase in EF was mainly and independently linked to a concomitant decline in TPVR (6-month change in mmHg.min.m(2).L(−1), EDV-/EF-: +1 ± 8, EDV+/EF-: +3 ± 9, EDV-/EF+: -7 ± 6, EDV+/EF+: -15 ± 20, p < 0.001) while the absence of any EF improvement was associated with high persisting rates of abnormally high TPVR at 6 months (EDV-/EF-: 31%, EDV+/EF-: 38%, EDV-/EF+: 5%, EDV+/EF+: 13%, p = 0.007). By contrast, the 6–month increase in EDV was mainly dependent on cardiac as opposed to vascular parameters and particularly on the presence of microvascular obstruction at baseline (EDV-/EF-: 37%, EDV+/EF-: 76%, EDV-/EF+: 38%, EDV+/EF+: 73%, p = 0.003). CONCLUSION: LV remodeling following reperfused MI is strongly influenced by the variable decrease in systemic vascular resistance under standard care vasodilating medication. The CMR monitoring of vascular resistance may help to tailor these medications for improving vascular resistance and consequently, LV ejection fraction. TRIAL REGISTRATION: NCT01109225 on ClinicalTrials.gov site (April, 2010).